The comprehensive geriatric assessment of an older adult with rheumatoid arthritis. Issue 2 (24th January 2022) - Zhang, Mufan; Feng, Min; Lai, Bei
Abstract: Introduction: The treatment of elderly‐onset rheumatoid arthritis (RA) pursues the same objectives as in younger patients: to control the symptoms, to prevent structural damage, to preserve function, and to decrease excess mortality. The presence of co‐morbidities is more specific in elderly patients with RA, which raises therapeutic challenges for physicians. Comprehensive geriatric assessment (CGA) is an essential tool that examines factors affecting the course of disease and the outcome of treatment. CGA includes the patient's functional, physical, mental, emotional, pharmacotherapeutic, and socioeconomic status. This article aims to present CGA in the evaluation and management of frail elderly patient with RA. Patient & Result: A case study of an 80‐year‐old man with RA and ILD is presented to describe the process of CGA and provides nutritional supplement therapy, patient education, and rehabilitation guidance to help patient progress from frailty to non‐frailty. Discussion: The case revealed that CGA provides physicians with information on the reversible area of frailty and the leading cause of deterioration in EORA. Key point: Our mainly point is focusing on assessing EROA patients' status with CGA and we treated patient by following the results of CGA.